A Domain-Specific Language for Multitask Systems, Applying Discrete Controller Synthesis. (19th March 2007) - Delaval, Gwenaël; Rutten, Éric
Abstract : We propose a simple programming language, called Nemo, specific to the domain of multitask real-time control systems, such as in robotic, automotive, or avionics systems. It can be used to specify a set of resources with usage constraints, a set of tasks that consume them according to various modes, and applications sequencing the tasks. We automatically obtain an application-specific task handler that correctly manages the constraints (if there exists one), through a compilation-like process including a phase of discrete controller synthesis. This way, this formal technique contributes to the safety of the designed systems, while being encapsulated in a tool that makes it usable by application experts. Our approach is based on the synchronous modelling techniques, languages, and tools.